(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The infrastructure is an important aspect in the Government sector and in the public sector. Therefore, the construction of roads, bridges, and all the related civil projects must be organized and systematic. Hence the Public Works Department (PWD) is the organization to handle these government projects. These projects are crucial as they help in the development of the country. For example, a well-constructed road will promote an efficient transportation system that will contribute to the economy of the country. It makes transportation and other operations easier through construction projects. It reduces unemployment by providing opportunities to people having different skills. Therefore, the Public Works Department holds great importance in the progress of the country.